Answered

Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

eliminate 3x+2y=4
8x-3y=-6


Sagot :

Steps:
1. Multiply the first line by 3 and the second by 2
3(3x + 2y= 4)
2(8x -3y=-6)
2. New lines are
9x + 6y= 12
16x + -6y=-12
3. Now add/subtract them
25x + 0= 0
25x=0
4. Divide by 25
X=0

5. To find y, substitute the 0 in the x in one of the equations
9x + 6y= 12
9(0) + 6y= 12
6y= 12
6. Divide by 6, your Y=2
7. X=0, Y=2